Ameloglyphics: A forensic tool for human identification - Nishath Sayed Abdul (Wolters Kluwer Medknow Publications, 2023)
Crime rates in our contemporary technological age have been rising at an alarming pace. Newer methods are needed to determine who the perpetrator and victim are in these situations. By comparing a person's recorded information with their own unique characteristics, automated biometric systems may determine who they are. Biometric identifiers like fingerprint and iris scanning are among the most reliable ways. Due to the vulnerability of soft tissues, these procedures cannot be depended on in the event of widespread calamities such as fires or gas leaks. Therefore, improved individual identification necessitates a biometric system based on the hard tissue. Thus, ameloglyphics was created to serve as a key tool in forensic odontology, particularly in the case of huge fatalities caused by natural catastrophes.